Post-drought moisture condition determines tree growth recovery after extreme drought events in the Tianshan Mountains, northwestern China - Guoju Wu; Guobao Xu; Bo Wang; Xiaohong Liu; Tuo Chen; Huhu Kang (Ecological Indicators, 2023)
Recently, forests in the Tianshan Mountains have shown a marked decline in growth and an increased mortality rate because of the more frequent and severe effects of extreme drought, which threatens the ecosystem services they provide. To achieve forest conservation and sustainable development benefits, it is crucial to understand the post-drought recovery trajectory of tree growth and its driving factors. In this study, we quantified the growth recovery performance of dominant tree species in the Tianshan Mountains after extreme drought events and determined the influences of climate factors on forest growth resilience using tree-ring proxy data. The results showed that post-drought moisture conditions may determine the post-drought growth recovery of trees. The post-drought growth for 1997 was higher than that for 1974, which may be attributed to the subsequent period of 1997 experiencing very high precipitation, whereas the year following the 1974 drought was dry (Standardized Precipitation Evapotranspiration Index < 0). Because of the more favorable climate conditions in the post-drought period, the observed relationship between resistance and recovery in 1997 showed a closer fit to the hypothetical “line of full resilience” which sets resilience to a constant value of 1, allowing trees to recover fully at any given value of resistance. Trees showed lower mean values of the tree growth recovery index (RC) and average recovery rate (ARR) and higher mean values of total growth reduction (TGR) and recovery period (RE) for the drought event in 1974 than that in 1997. We distinguished the relative influence of temperature and precipitation on different drought phases using Boosted Regression Tree (BRT) model. The results showed that the climate conditions during the drought year and subsequent precipitation variation were most influential variables for tree growth recovery. Specifically, post-drought precipitation explained up to 20 % of the variance in RC, TGR, RE, and ARR. These findings deepen our understanding of the impacts of prolonged drought on tree growth, which could aid in developing forest management and conservation strategies to respond to extreme drought.